Novel lipid antigens for NKT cells in cancer - Lee, Michael S.; Webb, Tonya J. (Frontiers in Immunology, 2023)
Cancer immunology aims to unleash the power of the immune system against tumors without the side effects of traditional chemotherapy. Immunotherapeutic methods vary widely, but all follow the same basic principle: overcome the barriers utilized by cancers to avoid immune destruction. These approaches often revolve around classical T cells, such as with CAR T cells and neoantigen vaccines; however, the utility of the innate-like iNKT cell in cancer immunotherapy has gained significant recognition. iNKT cells parallel classic T cell recognition of peptide antigens presented on MHC through their recognition of lipid antigens presented on the MHC Ilike molecule CD1d. Altered metabolism and a lipogenic phenotype are essential properties of tumor cells, representing a unique feature that may be exploited by iNKT cells. In this review, we will cover properties of iNKT cells, CD1d, and lipid antigen presentation. Next, we will discuss the cancer lipidome and how it may be exploited by iNKT cells through a window of opportunity. Finally, we will review, in detail, novel lipid antigens for iNKT cells in cancer.